INOVASI KUDAPAN KAKI NAGA MENGGUNAKAN BUAH SEMANGKA SEBAGAI BAHAN PENGGANTI DAGING AYAM - Nonot Yuliantoro; Billy Eagan; Steven Setiadi; Wisnuadji Wibowo (Jurusan Pariwisata Politeknik Negeri Kupang, 2022)
The aim of this product innovation research is to find out whether watermelon can be used as the basic ingredient of making kaki naga replacing chicken meat. The methods we are using in this research are hedonic and quality hedonic test which will be scored by an expert in the culinary scene which is still active today. There are in total 12 experts that will be helping us in conducting this research which is all from Westin Jakarta Hotel and is currently still actively working at the well-known 5-star hotel. The scale we will be using in this research is the Likert scale which scores from 1-5. The score given by the experts will be analyzed by finding the average or mean score given by those experts, which will be continued by the validity and reliability test. The result of this research is positive which can be seen by the average score given by the experts which also means that the product innovation of creating kaki naga by using watermelon can replace chicken meat as its basic ingredient.